2022
DOI: 10.3389/fimmu.2022.807326
|View full text |Cite
|
Sign up to set email alerts
|

The ECSIT Mediated Toll3-Dorsal-ALFs Pathway Inhibits Bacterial Amplification in Kuruma Shrimp

Abstract: The Toll signaling pathway plays an important role in animal innate immunity. However, its activation and signal transmission greatly differ across species and need to be investigated. Shrimp farming is a worldwide economic activity affected by bacterial disease from the 1990s, which promoted research on shrimp immunity. In this study, we first proved that, among the three identified Toll receptors in Marsupenaeus japonicus kuruma shrimp, Toll 3 plays a pivotal role in initiating the antibacterial response in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The increase in expression of low-density lipoprotein receptor (LRP1)-related protein 1 indicates its involvement in pathogen recognition and immune regulation [123]. The activation of the MAPK and Toll pathways is in accordance with previous research, highlighting their importance in immune responses [124][125][126][127]. On the other hand, antimicrobial peptides (AMPs) played a crucial role in both strains, especially anti-lipopolysaccharide factors (ALFs) and lysozymes, which contribute to bacterial [130] and fungal [131] defenses.…”
Section: Differentially Expressed Transcripts Are Involved In the Imm...supporting
confidence: 85%
“…The increase in expression of low-density lipoprotein receptor (LRP1)-related protein 1 indicates its involvement in pathogen recognition and immune regulation [123]. The activation of the MAPK and Toll pathways is in accordance with previous research, highlighting their importance in immune responses [124][125][126][127]. On the other hand, antimicrobial peptides (AMPs) played a crucial role in both strains, especially anti-lipopolysaccharide factors (ALFs) and lysozymes, which contribute to bacterial [130] and fungal [131] defenses.…”
Section: Differentially Expressed Transcripts Are Involved In the Imm...supporting
confidence: 85%
“…Hence, the Toll3-ECSIT-Dorsal-ALFs pathway was required to confer antibacterial immunity in shrimps. 318 The inhibition of the expression of AMPs such as ALF, Cru and Lys was also confirmed in the Toll knockdown and Toll + ECSIT double knockdown model of E. carinicauda after the bacteria V. parahaemolyticus infection. 319 In another significant finding, Toll2 from P. clarkii regulates the expression of AMPs such as ALF1 and ALF2 by promoting the nuclear import of activating transcription factor 4 (ATF4), which is a member of the ATF/CREB transcription factor family 36 (Figure 4).…”
Section: Down Syndrome Cell Adhesion Moleculementioning
confidence: 74%
“…In P. japonicus , Toll3 but not Toll2 or Toll1 interacts downstream with evolutionarily conserved signalling intermediate in Toll pathway (ECSIT) protein after the challenge of Gram‐positive bacteria S. aureus to regulate the expression of ALF5 and ALF6 via the canonical NF‐κB factor Dorsal (not shown). Hence, the Toll3‐ECSIT‐Dorsal‐ALFs pathway was required to confer antibacterial immunity in shrimps 318 . The inhibition of the expression of AMPs such as ALF, Cru and Lys was also confirmed in the Toll knockdown and Toll + ECSIT double knockdown model of E. carinicauda after the bacteria V. parahaemolyticus infection 319 .…”
Section: Toll‐nf‐κb Signalling In Crustacean Innate Immunitymentioning
confidence: 82%
“…Immune functions of ECSIT are conserved across the species, as it is vital in offering protection against bacterial, virus, and fungal infections in the lower chordate suggesting the importance of ECSIT in immune mechanisms (Ding et al, 2022;Ge et al, 2021;Qu et al, 2015;Y. Lin et al, 2011).…”
Section: Role Of Ecsit In Innate Immunitymentioning
confidence: 99%
“…Studies have demonstrated that PRDX1 interaction with TRAF6 leads to TRAF6 mediated ubiquitination of ECSIT, which is critical in activation of NF‐ϰB and autophagy in response to TLR‐4 stimulation (Min et al, 2018). Immune functions of ECSIT are conserved across the species, as it is vital in offering protection against bacterial, virus, and fungal infections in the lower chordate suggesting the importance of ECSIT in immune mechanisms (Ding et al, 2022; Ge et al, 2021; Qu et al, 2015; Y. Lin et al, 2011). Recent studies on crustaceans unveil its antibacterial role along with TRAF6, which was inhibited through miRNA224 (Gong et al, 2021) Figure 2a.…”
Section: Role Of Ecsit In Cellular Physiologymentioning
confidence: 99%